TRADITIONAL MATRIAL ART OF LANGGA - Syamsudin Mopangga; Hartono Hadjarati; Suprianto Kadir (Jambura Journal of Sports Coaching, 2020)
This study aims to analyze Langga as traditional martial arts of the Bone Bolango community. This research is a survey research. The research subjects were Langga teachers, and the surrounding community. Data collection techniques are done using interview techniques by asking questions. The results of this study are that Langga Self-Defense is a typical silat of the Bone Bolango community which was inherited by the ancestors of Bone Bolango who is also a martial art for maintaining security in the territory of the Bone Bolango kingdom. The conclusion is that Langga martial arts is a tradition of the Bone Bolango community. The existence of Langga martial arts had existed in the 1960s which at that time was played by Temeapusa and Syahrul Panipi. In 1993 until now Langga's martial arts began to be rarely played again especially in welcoming the big days.